The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.3390/diagnostics12123038
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Automatic Deep-Learning-Based Lung Analysis on Quantification of Interstitial Lung Disease: Correlation with Pulmonary Function Test Results and Prognosis

Abstract: We investigated the feasibility of a new deep-learning (DL)-based lung analysis method for the evaluation of interstitial lung disease (ILD) by comparing it with evaluation using the traditional computer-aided diagnosis (CAD) system and patients’ clinical outcomes. We prospectively included 104 patients (84 with and 20 without ILD). An expert radiologist defined regions of interest in the typical areas of normal, ground-glass opacity, consolidation, consolidation with fibrosis (traction bronchiectasis), honeyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…However, in ILD, a simple density mask approach cannot effectively distinguish the lung from the chest wall due to lesions with high attenuation, such as consolidation and fibrosis [ 90 ]. Therefore, it is recommended to employ dedicated software for the automatic segmentation of the lung, as mentioned above [ 78 , 82 , 85 , 91 ].…”
Section: Ct Analysis Of Ildmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in ILD, a simple density mask approach cannot effectively distinguish the lung from the chest wall due to lesions with high attenuation, such as consolidation and fibrosis [ 90 ]. Therefore, it is recommended to employ dedicated software for the automatic segmentation of the lung, as mentioned above [ 78 , 82 , 85 , 91 ].…”
Section: Ct Analysis Of Ildmentioning
confidence: 99%
“…The BV5% value, calculated as the proportion of BV5 to total BV, was found to be a prognostic factor for adverse outcomes (intubation or mortality) in patients with COVID-19 [ 139 ]. In thin-section CT scans of COVID-19 pneumonia, bilateral distribution and subsegmental vessel enlargement are usually observed in clinical situations [ 85 , 140 , 141 ]. These vascular abnormalities are consistent with the results of dual-energy CT [ 142 , 143 ] and microvascular observations using video microscopy [ 143 ].…”
Section: Thin-section Ct Analysis For Covid-19 Pneumoniamentioning
confidence: 99%
“…Additionally, regarding the risk of malignancy development or coexistence, in a recent study of Liang et al, it is mentioned that whole-lung CT texture analysis is a promising tool for the lung cancer risk stratification of IPF patients [ 32 ]. Moreover, Aoki et al [ 33 ] using deep-learning-based analysis and measured consolidation with fibrosis, found that it was independently associated with poor survival. They also found that the lesion extent measured using deep-learning-based analysis showed a negative correlation with pulmonary function test results and prognosis.…”
Section: Ai Applications In Ild Researchmentioning
confidence: 99%
“…A summarizing table (Table 1) for the included studies has been added at the end of this section. [30] Prognosis 465 patients Imaging -Budzikowski et al [31] Prognosis 169 patients Imaging and Genomic -Liang et al [32] Prognosis 116 patients Imaging AUC = 0.870 Aoki et al [33] Prognosis 104 patients Imaging -Bowman et al [34] Prognosis 589 patients Proteomic Sensitivity: 90% Mayr et al [35] Prognosis 124 patients Proteomic Accuracy: 83%…”
Section: Ai Applications In Ild Researchmentioning
confidence: 99%
“…AI-based image analysis has advantages in terms of high reliability and reproducibility over other methods. Furthermore, indices derived from AI-based image analysis have been associated with pulmonary function decline, exacerbation, and prognosis in ILD [11][12][13]. Artificial intelligence based quantitative CT image analysis software (AIQCT) is an AI-based image analysis software that can automatically classify chest CT images into normal lung, ground-glass opacities (GGOs), reticulations, consolidations, honeycombing, nodules, hyperlucencies, interlobular septum, bronchi, and vessels [14].…”
Section: Introductionmentioning
confidence: 99%